Program Berkelanjutan Membantu Mitra KWT Melati Mini untuk Tumbuh Kembang dengan Usaha Ternak Puyuh di Koto Lua Kecamatan Pauh, Padang - Mirnawati Mirnawati; Yurniwati Yurniwati; Zuhri Syam (Warta Pengabdian Andalas, 2020)
The problems faced by farmers are the high price of feed and the socio-economic problems of livestock. The solutions offered are counseling, application of ration technology and assistance related to science of feed (nutritious and low-priced feed formulations), application of ration formulas by breeders, guidance and counseling on socio-economic problems for instance entrepreneurship, marketing and business development. The objective of the activity is to increase farmers' knowledge about rations (low price ration formulations) and socio-economic problems of livestock. Meanwhile, the benefit of the activity is to help develop the quail farming micro business as a form of institutional care for the community around the campus and to improve community service performance and the application of University’s innovation. The stages of the activity implementation began with counseling on quail farming, counseling on rations and application of ration formulation technology, and evaluation. The results of the activity indicated that the extension activities carried out had increased farmers' knowledge about low-priced feed and ration formulations. In addition, counseling in the economic sector is able to provide knowledge to farmers about entrepreneurship for their livestock businesses.